Terror Management in a Multicultural Society: Effects of Mortality Salience on Attitudes to Multiculturalism Are Moderated by National Identification and Self-Esteem Among Native Dutch People - Tjew-A-Sin, Mandy; Koole, Sander Leon (Frontiers in Psychology, 2018)
Terror Management Theory (TMT; Greenberg, Solomon, & Pyszczynski, 1997) proposes that mortality concerns may lead people to reject other cultures than their own. Although highly relevant to multiculturalism, TMT has been rarely tested in a European multicultural society. To fill this void, two studies examined the effects of mortality salience (MS) among native Dutch people with varying levels of national identification and self-esteem. Consistent with TMT, MS led to less favorable attitudes about Muslims and multiculturalism among participants with high (rather than low) national identification and low (rather than high) self-esteem (Study 1). Likewise, MS led participants with high national identification and low self-esteem to increase their support of Sinterklaas, a traditional Dutch festivity with purported racist elements (Study 2). Together, these findings indicate that existential concerns may fuel resistance against multiculturalism, especially among people with low self-esteem who strongly identify with their nationality.